CARA MENGAJAR YESUS DALAM LUKAS 10:25-37 SEBUAH MODEL PEDAGOGI BAGI PARA PENGAJAR - Luturmas, Johanis; Doteua, Adriwanti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2022)
It is undeniable that teacher plays an important role in not only transfer of knowlede, but also forming the students to be human in all his dimention. Recently Indonesia gives special attention to teachers because of his role in human formation.In His earthly life Jesus is always entitled as teacher, even as the greatest teacher. People ini his time always call him teacher. His way of teaching is really apreciated. He knew very well his students or everyone came to him asking for his opinion or his teaching. His teaching depended on whom he met. To the one who is stone headed, Jesus gives strong respong, but to the one who is meek, he sometimes opens mind for dialogue.For christian religious teachers or cathecists, Jesus is always seen as an exemplary teacher. Therefore in this writing his way of teaching will be analysed based on the pericope of Luke 10:25-30 in order to express his manner of teaching that will become the example for teachers in this modern era.The key words: teacher, learning, the way of teaching.